Molybdenum rods assembled with nanosheets: a high catalytic material for phenol sensing. (December 2020) - Wahab, Rizwan; Khan, Farheen; Ahmad, Naushad; Alam, Manawwer
Abstract: The phenol (PhOH) is a toxic chemical and can affect to the environment and human directly and indirectly. Due to their toxic nature it is listed as a carcinogenic compound for human health. The sensitivity of the PhOH in liquid medium can be detemine through various techniques in liquid medium was detected through various techniques for instance HPLC, mass, fluorescence and spectrophotometry etc but all of these techniques are expensive and not easily available to detect the longer range of samples in a very less time. To keep this view the present manuscript was designed to shows the utilization of metal oxide nano and microstructures as sensor material, therefore, initially highly crystalline molybdenum oxide rods assembled with nanosheets (referred to as α-MoO3 RANs) was synthesized via solution process and utilized for sensing against PhOH. The α-MoO3 RANs exhibit numerous applications in various directions such as catalyst, LEDs, Field emission devices, batteries etc. The α-MoO3 RANs were formed from the solution processes in a short time span. The formed powder was well characterized through the techniques such as XRD, SEM, TEM and FTIR. From the analysis, it reveals that the size of each NS is ∼200 nm in diameter whereas rods shaped structures length goes to 2–6 μm with good structural and chemical characteristics. The crystalline α-MoO3 RANs were applied for the electro chemical studies as three electrode system (GCE as working electrode, Ag/AgCl as reference and pt wire as counter electrode) with PhOH as an analyte in PBS. The electrochemical studies were conducted through cyclic voltammetry (CV) in terms of their low to high conc-entration ranges from 7.8 to 1000 μM in PBS, scan rate at different potential from 5 to 100 mV with the α-MoO3 RANs based working electrode (α-MoO3 RANs/GCE). The designed working electrode sensor having excellent reproducibility, sustained in presence of 62.25 μM (PhOH) for seven consecutive cycles. Including this, the chronoamperometry (0–1500 s ) and electrochemical impedance spectra (EIS) were also analyzed. A probable mechanism was also discussed based on the analysis and their observations. Graphical abstract: Image 1 Highlights: The molybdenum rods assembled with nanosheets (α-MoO3 RANs) were prepared via solution process. α-MoO3 RANs were well characterized via XRD, SEM, TEM, FTIR and CV spectroscopy. The α-MoO3 RANs were employed for sensing against phenol at low to high conc. Chronoamperometry, electrochemical impedance (EIS), cycle response were studied. Possible sensing mechanism also explained for the phenol with α-MoO3 RANs.